Use of Internet Protocol version 6 to Provide Better Communication Networking System for Railway Operation - YUSRI, ALYAH AMYRAH; Nagarajoo, Karthigesu; Yahya, Muhammad Nazrin (Progress in Engineering Application and Technology, 2023)
First Internet Protocol (IP) was introduced in 1981 by Internet Engineering Task Force (IETF) with providing more than 4.3 billion IP addresses. However, after 25 years of deployment IPv4 connection start to exhausted as the number of IP address drained as year pass. IETF encounter this problem with providing new Internet Protocol (IPv6) who capable to provide at least 340 trillion addresses. It way greater than IPv4 and the believe is that those address will not run out in future. With focus on providing better network communication system in railway, ping test and latency test being execute for this research to prove effectiveness of IPv6 in term of latency. The results show that, compared to IPv4, IPv6 have lower round-trip time (RTT) in the ping test and in the latency test. However, in a condition of testing (time taken of 60 s), IPv6 shows higher latency than IPv4 which it contradicts with the theoretical of IPv6 in providing efficient data transferring. Details explanation of the reason why IPv6 shows different result of latency in condition of experiment are explain in the result. At the end of this project, it proves that IPv6 have better in data transferring with lower latency than IPv4 in applications of railway industry.